Development and optimization of in-situ gels for vaginal delivery of metronidazole and curcumin via box-behnken design: In vitro characterization and anti-trichomonas activity - Pozharani, Leyla Beba; Baloglu, Esra; Suer, Kaya; Guler, Emrah; Burgaz, Vildan; Kunter, Imge (Elsevier, 2023)
The aim of this study was to develop and optimize vaginal poloxamer in-situ gel formulations with metronidazole and curcumin combination for the treatment of infections caused by parasitic protozoa, Trichomonas vaginalis. Protozoan parasite infections cost the globe a colossal burden in terms of human and animal health. Lack of medication in low-income countries and rising drug resistance are posing substantial challenges in control and eradication of this infection. Today there is a tremendous drift in new alternative/synergic treatment strategies. Combination treatment, in particular, appear to be a promising approach against persistent, common, and infectious diseases like T. vaginalis. Poloxamer in-situ gels were prepared and optimized using the Box-Behnken statistical experiment design concept. The effect of critical parameters on critical quality features were evaluated by measuring the Tsol-gel transition temperature, solubilizing capacity of active substances in poloxamer bases, plastic viscosity, dynamic viscosity, and yield values. Optimized formulations (OPT-F1; F2; F3) were also tested for flow and mechanical properties, in-vitro release properties, cytotoxicity against the SK-HEP-1 cell line, and antiparasitic activity. The optimum formulations include properties that make them appropriate for vaginal administration and have been shown to be non-cytotoxic. The candidate gel formulation (OPT-F3) demonstrated statistically significant in-vitro activity against T. Vaginalis viability, demonstrating its antiparasitic effect. Stability studies conducted at 4 degrees C and 25 degrees C temperatures revealed that the ideal formulations retained their stability for 90 days. The study found that the gel containing metronidazole and curcumin is an effective and innovative approach to treating trichomoniasis and advances scientific research in this field.
Keywords: Trichomonas vaginalis; Curcumin; Metronidazole; poloxamer in-situ gels; Vaginal drug delivery; Box-behnken design